Information Asymmetry and Co-Creation in Health Care Services. Issue 3 (August 2014) - Barile, Sergio; Saviano, Marialuisa; Polese, Francesco
With the aim of addressing a gap in service research on co-creation in health care, this study discusses the problem of information asymmetry in the service provider–user relationship by adopting the Viable Systems Approach. We develop a three-step interpretative framework to support the understanding of the health service relationship by going beyond the traditional information asymmetry view towards a framework capable of examining the human side of service interaction. Using the case of the Italian Health System, we discuss whether and how the problem of information asymmetry affects the health care provider–user co-creation relationship. Our findings open up a wider view of information asymmetry, suggesting a shift in focus from information sharing to interpretation schemes sharing, all the way up to values sharing, offering new insights for co-creation in health care.